ANALYZING THE EFFECTIVENESS OF CHATGPT AND OTHER ARTIFICIAL INTELLIGENCE TOOLS IN LANGUAGE TEACHING - Zulfizar Rustamovna Karimova (Modern American Journals, 2025)
This article analyzes the role and effectiveness of artificial intelligence technologies, in particular generative language models such as ChatGPT and modern digital learning tools such as Duolingo Max, Gemini, replica, in the language teaching process. In the course of the study, the results of students studying on the basis of traditional methods are compared with students studying using SI-based educational tools. The benefits, limitations, pedagogical and ethical aspects of using AI tools are also explored and recommendations are made for effective integration into the educational process.
Keywords: Artificial intelligence, ChatGPT, digital education, language teaching, adaptive teaching, generative model.